Moroccan Households in the World Economy : Labor and Inequality in a Berber Village - Crawford, David, 1965- (Book collections on Project MUSE., 2008)
In the High Atlas Mountains of Morocco, far from the hustle and noise of urban centers, lies a village made of mud and rock, barely discernible from the surrounding landscape. Yet a closer look reveals a carefully planned community of homes nestled above the trees, where rock slides are least frequent, and steep terraces of barley fields situated just above spring flood level. The Berber-speaking Muslims who live and farm on these precipitous mountainsides work together at the arduous task of irrigating the fields during the dry season, continuing a long tradition of managing land, labor, and.